2008
DOI: 10.1186/1748-717x-3-44
|View full text |Cite
|
Sign up to set email alerts
|

[(18)F]Fluoroethyltyrosine- positron emission tomography-guided radiotherapy for high-grade glioma

Abstract: Background: To compare morphological gross tumor volumes (GTVs), defined as pre-and postoperative gadolinium enhancement on T 1 -weighted magnetic resonance imaging to biological tumor volumes (BTVs), defined by the uptake of 18 F fluoroethyltyrosine (FET) for the radiotherapy planning of high-grade glioma, using a dedicated positron emission tomography (PET)-CT scanner equipped with three triangulation lasers for patient positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 40 publications
1
51
0
8
Order By: Relevance
“…Therefore, the fluorinated amino acid analog 18 F-FET has emerged as a powerful complementary tool for glioma imaging (21,22). 18 F-FET PET was shown to be useful for biopsy and treatment planning by accurate delineation of the tumor borders and demarcation of most malignant tumor parts (11,21,(23)(24)(25) and for subsequent treatment monitoring including differentiation between benign therapyinduced changes and tumor recurrence (13,18,(26)(27)(28). Furthermore, the additional use of kinetic analysis of 18 F-FET PET was shown to enable more accurate tumor grading, even in individual patients: increasing time-activity curves are considered to be associated with less malignant low-grade glioma tissue, whereas decreasing timeactivity curves were shown to be prevalent in more aggressive high-grade glioma tissue (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fluorinated amino acid analog 18 F-FET has emerged as a powerful complementary tool for glioma imaging (21,22). 18 F-FET PET was shown to be useful for biopsy and treatment planning by accurate delineation of the tumor borders and demarcation of most malignant tumor parts (11,21,(23)(24)(25) and for subsequent treatment monitoring including differentiation between benign therapyinduced changes and tumor recurrence (13,18,(26)(27)(28). Furthermore, the additional use of kinetic analysis of 18 F-FET PET was shown to enable more accurate tumor grading, even in individual patients: increasing time-activity curves are considered to be associated with less malignant low-grade glioma tissue, whereas decreasing timeactivity curves were shown to be prevalent in more aggressive high-grade glioma tissue (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…For this application, amino acid and nucleoid tracers are better suited (123)(124)(125)(126)(127). Several studies suggested that outcomes are better for patients in whom 11 C-MET or 18 F-FET PET coregistered to MRI are applied for treatment planning and follow-up than for patients diagnosed by MRI alone (123)(124)(125)(126)128). In the follow-up and for the management of patients with brain tumor, the differentiation between recurrent tumor as a sign of treatment failure and necrosis as an indicator of success is essential.…”
Section: Monitoring Treatment Effects Petmentioning
confidence: 99%
“…53 Manual delineation of target volumes using different window-level settings and look-up tables is the most common and widely used technique in the clinic; however, the method is highly operator-dependent and is subject to high variability among operators. Rather large intraobserver variability was reported 54 for many localizations, including high-grade glioma (HGG), as shown in Fig. 6.…”
Section: Pet Image Segmentation Techniquesmentioning
confidence: 92%